Mechanisms involved in regulation of periodontal ligament cell production of pro‐inflammatory cytokines: Implications in periodontitis - Bengt‐Olof Nilsson (2020)
It is well recognized that human periodontal ligament cells (PDL cells) may represent local immune cells of the periodontal tissues. However, it is unclear whether they represent "true" immune cells, since they can produce pro-inflammatory cytokines not only after stimulation with bacterial lipopolysaccharides but also in response to other stimuli such as mechanical stress. Stimulation with bacterial lipopolysaccharides strongly enhances PDL cell production of pro-inflammatory cytokines through activation of toll-like receptors and NF-κB signaling. Less information is available regarding putative modulators of cytokine production and their mechanisms of action in PDL cells. The anti-inflammatory glucocorticoid dexamethasone reduces lipopolysaccharide-induced PDL cell production of cytokines. Recent observations show that vitamin D and the antimicrobial peptide LL-37 antagonize lipopolysaccharide-stimulated PDL cell production of pro-inflammatory cytokines. Secretory leukocyte protease inhibitor is endogenously expressed by PDL cells, and this protein negatively regulates PDL cell-evoked cytokine production. More information and knowledge about the regulation of PDL cell production of cytokines may clarify the role of PDL cells in oral innate immunity and their importance in periodontitis.